Advances in child development and behavior. (Advances in child development and behavior, 2006)
Volume 34 of the Advances in Child Development and Behavior series is divided into eight components that highlight some of the most recent research in developmental and educational psychology. A wide array of topics are discussed in detail, including social stereotypes and prejudice, phonetic and lexical learning, poverty, the development of moral thinking, and others. Each component provides in depth discussions of various developmental psychology specializations. This volume serves as an invaluable resource for psychology researchers and advanced psychology students. *Goes in depth to address eight different developmental and educational psychology topics *A necessary resource for both psychology researchers and students.